Environmental science practices integrated with IK: The case of soot (Namibia Educational Reform Forum Journal, 2020)
The integration of IK in science practices, in which various cultural practices, artefacts and science language reflecting western science indigenous communities (IC) use, is sometimes not well-explained to learners. Consequently science teachers grapple to incorporate IK with science concepts in the curriculum. In this study, global warming due to soot ranking second only to carbon dioxide is investigated, to see how ideas IC use can be incorporated into environmental science classrooms. Activities in which IC interact with soot are there in the community but not documented. For instance, indigenous communities discourage one another to fetch water from a water source using a soot-contaminated container. To understand more of this cultural practice in order to successfully incorporate knowledge advanced and used; this study used brain storming, practical work, interviews and reflections to generate data. Activities IC engage in were incorporated as case studies and practical activities in in Grade 11 science practices, first by teachers and then by learners. In doing so, a culturally responsive pedagogical style emerged. Investigation emerged ideas indigenous communities use and how their incorporation into environmental science/teaching practices were achieved and possibly assisted in reducing global warming. Findings were IC cultural practices related to soot can be incorporated in teaching concepts of global warming and also, such approach brings about culturally responsive pedagogical styles.
Keywords: soot; truth theories; global warming; practices; indigenous communities